2019
DOI: 10.2147/ott.s220621
|View full text |Cite
|
Sign up to set email alerts
|

<p>Upregulated miR-27a-3p Indicates a Poor Prognosis in Pancreatic Carcinoma Patients and Promotes the Angiogenesis and Migration by Epigenetic Silencing of GATA6 and Activating VEGFA/VEGFR2 Signaling Pathway</p>

Abstract: BackgroundAbnormal miR-27a-3p expression has been frequently reported in several types of human cancer and contributes to tumor progression. However, the role and potential molecular mechanism of miR-27a-3p in the progression of pancreatic carcinoma have not been clarified.Materials and methodsThe expression of miR-27a-3p and GATA binding protein 6 (GATA6) in pancreatic carcinoma tissues and cell lines was evaluated by quantitative real-time PCR and Western blotting analysis. The relationship between clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…20 In addition, upregulating the expression of miR-27a-3p indicates a poor prognosis in pancreatic carcinoma patients and promotes the angiogenesis and migration by epigenetic silencing of GATA6 and activating VEGFA/ VEGFR2 signaling pathway. 21 Furthermore, it has been shown that miR-143-3p targeting of ITGA6 suppresses tumor growth and angiogenesis by downregulating PLGF expression via the PI3K/AKT pathway in gallbladder carcinoma. 22 In this study, we also found that miR-15b-5p, miR-27a-3p, miR-143-3p, and miR-627-5p were closely related with PVT1 and NOP2.…”
Section: Discussionmentioning
confidence: 99%
“…20 In addition, upregulating the expression of miR-27a-3p indicates a poor prognosis in pancreatic carcinoma patients and promotes the angiogenesis and migration by epigenetic silencing of GATA6 and activating VEGFA/ VEGFR2 signaling pathway. 21 Furthermore, it has been shown that miR-143-3p targeting of ITGA6 suppresses tumor growth and angiogenesis by downregulating PLGF expression via the PI3K/AKT pathway in gallbladder carcinoma. 22 In this study, we also found that miR-15b-5p, miR-27a-3p, miR-143-3p, and miR-627-5p were closely related with PVT1 and NOP2.…”
Section: Discussionmentioning
confidence: 99%
“…[25,[32][33][34] Mir-27a-3p has been identi ed to promote tumor invasion and metastasis in gastric, colon, pancreatic, and nasopharyngeal cancers. [35][36][37][38] On the other hand, a tumor suppressor role has also been shown for miR-27a-3p in some cancers. For instance, it inhibits the proliferation of non-small cell lung cancer cells by targeting HOXB8.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that miR-27-3p promotes and suppresses the metastasis of pancreatic cancer and hepatocellular carcinoma, respectively [ 80 , 81 ], suggesting the dual role of this miRNA in a cellular context-dependent manner. Another study showed that the anchorage-independent growth of osteosarcoma cells is accelerated by miR-27-3p, whose expression is upregulated in cancer cells in comparison with normal osteocyte cells [ 31 ].…”
Section: Mirnas Positively Regulating Anoikis Resistance and Anchomentioning
confidence: 99%